تأثير مستخلص خشب المسكة Robinia pseudoacacia L في الفطريات المرافقة للصنف شام 8 المزروع في منطقة الغاب - الناصر, زكريا; الحكيم, وسيم; بركات, رشا (Latakia University Journal -Biological Sciences Series, 2017)
أجري هذا البحث خلال الفترة بين 2014-2016 بكلية الزراعة بجامعة دمشق وهدف إلى تأثير مستخلص المسكة على الفطريات المرافقة للقمح صنف شام 8 المزروع في منطقة الغاب.حيث أظهرت النتائج تباين في نسبة المادة المستخلصة من العينات الخشبية للمسكة. إذ كان وزن المادة الجافة (432.23مغ) (716.95مغ) لكل من الخشب العصاري والخشب القلبي على الترتيب، وجد أن أهم الفطريات المرافقة لحبوب القمح المجموعة هي : Fusarium sp.(36%) و Alternaria sp. (28%) و Aspergillus sp. (12%) وRhizopus sp (9%) وPenicillium sp (6%) وفطريات غير معرفة بنسبة (9%)، ودلت النتائج على أنّ المستخلصات الخشبية للمسكة تباينت في تثبيط نمو الميسليوم للفطريات المختبرة (Fusarium sp. و Alternaria sp. و Aspergillus sp.) في الوسط المغذي وفقاً لنوع المستخلص والتركيز والفطر المستهدف. وقد ازداد تأثير مستخلصات الخلائط الخشبية بزيادة نسبة المادة الجافة للخشب القلبي فكلما زادت نسبة الخشب القلبي زاد التأثير المثبط في نمو الفطريات. ازدادت فاعلية الخلائط بزيادة تركيز الخشب القلبي. وجد من البيانات اختلاف التركيز النصفي لمستخلصات الخشب القلبي والخشب العصاري والخلائط الخشبية بشكل كبير. فقد أعطى مستخلص الخليط الخشبي (10:10) أعلى فاعلية بين المستخلصات المختبرة على الفطريات الثلاثة، حيث كانت قيم EC50 أقل من 46.50 و 84.66 و139.54 ppm لكل من الفطريات Aspergillus sp. و Fusarium sp. و Alternaria sp. على الترتيب. بالمقابل أعطى مستخلص الخشب العصاري للمسكة أقل فاعلية على الفطريات المختبرةThe results showed a variation in the ratio of dry material derived from wood samples of (Robinia pseudoacacia L.). The dry matter weight was (432.23 mg) (716.95 mg) for each of the waterless wood and internal wood respectively.It was found that the most important fungi associated with wheat seed group are: Fusarium sp. (36%) and Alternaria sp. (28%) and Aspergillus sp. (12%) and Rhizopus sp (9%) and Penicillium sp (6%) and fungi are not defined by (9%).It was found that the wood extracts from (Robinia pseudoacacia L.) varied in the of the Almiceleom inhibition to the tested fungi growth (Fusarium sp. , Alternaria sp. and Aspergillus sp.) in the nutritious environment according to the type of the extracts, concentration and targeted fungi. The effect of the wood extracts has increased as the percentage of the dry matter of the heart wood increased. The incremental heart wood ratio increased inhibitory effect on the growth of fungi. On the other hand, the wood extract gave of waterless wood less effect of Miceleom inhibiting on the growth of tested fungi in general. The effectiveness of the mixtures Increased as heart wood concentration increased. It has been Found from the data that there was difference in migraine concentration of the heart wood extracts and waterless wood mixtures largely. the Extract of the mixture wooden gave (10:10) the highest efficiency among the three tested extracts on the fungus, where the EC50 values were less than 46.50, 84.66 and 131.54 ppm for each of the fungus (Aspergillus sp., Fusarium sp. And Alternaria sp. respectively.